PENGOLAHAN LIMBAH CAIR TAHU MENJADI BIOGAS SEBAGAI BAHAN BAKAR ALTERNATIF PADA INDUSTRI PENGOLAHAN TAHU - Oesman Raliby; Retno Rusdjijati; Imron Rosyidi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
Trunan is one of the biggest tahu industrial centers in Magelang. Nevertheless, the number of tahu manufacturer in this neighborhood is decreasing as the result of the unreachable price of the raw material and the lack of sawdust, which is used as the fuel. On the other side, the industry also causes environmental problem since the liquid wastes, as the side effect of tahu producing process, commonly is simply littered to the waters. As the result, the waters become polluted as well as the groundwater which is indicated by the dirtiness of the waters and stinky smell. To help solving the above problem, we hold a research with objective to make use of tahu liquid wastes as an alternative fuel. Based on some researches, liquid wastes of tahu liquid wastes as an alternative fuel. Based on some researches, liquid wastes of tahu contain methane more than 50% that makes it possible to become the raw material of biogas energy. The method used in this research is engineering method (design activity) which is not routine, thus there will be new contribution either for the process and the product/protptype. The result of the research shows that to produce 1500 liter of biogas that fulfills the average need of a household it takes 100 kg of soybean per day. Hence, for each cooking process of tahu which needs 30.000 kg of soybean produces 283,8 m3 of liquid wastes per day, which then produce 442,650 liter of biogas. Afterward, to steam 100 kg of soybean it takes 3,93 m3 of biogas, while it takes 20 kg of sawdust. Every 100 kg of soybean takes energy which costs Rp. 40.000 for 3 times cooking process and each process takes 0,2 m3 of sawdust which costs Rp. 12.500. Therefore, the efficiency reach 61,1%. Moreover, beside used as fuel to cook, biogas can also be used for other need like lights.